Studies on Economic and Monetary Problems and on Banking History: No. 21 (Mainze, Germany: Hase & Koehler Verlag, 1986)
The book provides a detailed theories on economic and monetary issue that affects the banking system.
include Index
osc 14/7/17
Loans
Keywords: Economics